Pola Konsumsi Rumah Tangga Petani Padi di Desa Ketawang Kecamatan Gondang Kabupaten Nganjuk - Dwi Indah Febriyani; Sri Widayanti; Hamidah Hendrarini; Nisa Hafi Idhoh Fitriana (AGRIMOR, 2022)
Rural is an area dominated by economic activities in agriculture. Ketawang Village is one of the rural areas in Gondang District where most of the residents work as farmers. Farming households have several challenges in trying to meet the consumption needs of their households. Various kinds of household expenditure or consumption needs that need to be allocated both for food consumption and non-food, savings and also household investment together will influence each other according to which priorities must be met first. The objectives of this study are 1) Describing the household characteristics of rice farmers, 2) Analyzing the consumption patterns of rice farmers' ladders in Ketawang Village. Primary data was obtained from interviews of 57 rice farmers who have characteristics, namely farmers who own and cultivate land. The number of samples is determined by 10% of the total population. Data processing and analysis methods with descriptive analysis with tabulation methods and multiple linier regression analysis. The result of this study is that the household consumption of rice farmers in Ketawang Village Gondang District Nganjuk Regency is dominated by expenditure on non-food consumption. Food expenditure was generated at 31.61% and expenditure, consumption, for non-food was 68.39%. This means that almost most rice farmers use their income for non-food consumption.